The Influence of Green Marketing and Brand Image on Purchasing Decisions - Zahara, Rita (Siber International Journal of Digital Business (SIJDB), 2024)
The purpose of this study was to determine whether green marketing affects purchasing decisions, to determine brand image affects purchasing decisions and to determine the effect of green marketing and brand image on purchasing decisions for Tupperware on Jalan Buah Batu. The population in this study is the surrounding community who purchased Tuppaware products for 2020 on Jalan Buah Batu Lingkungan I as many as 1718 people, where 94 people were sampled using the slovin formula. The data collection technique used in this study was carried out by distributing questionnaires. The analysis technique used in this research is multiple linear regression, partial test (t test), simultaneous significance test (F test) and the coefficient of determination. The results showed that partially Green Marketing has a positive and significant effect on Tupperware Purchasing Decisions, Brand Image has a positive and significant effect on Tupperware Purchasing Decisions and simultaneously Green Marketing and Brand Image have a significant effect on Tupperware Purchasing Decisions on Jalan Buah Batu.